2019
DOI: 10.1016/j.cub.2018.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-18B Promotes the Assembly of Myosin II Stacks for Maturation of Contractile Actomyosin Bundles

Abstract: SUMMARY Cell adhesion, morphogenesis, mechanosensing, and muscle contraction rely on contractile actomyosin bundles, where the force is produced through sliding of bipolar myosin II filaments along actin filaments. The assembly of contractile actomyosin bundles involves registered alignment of myosin II filaments and their subsequent fusion into large stacks. However, mechanisms underlying the assembly of myosin II stacks, and their physiological functions have remained elusive. Here we identified myosin-18B, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 45 publications
(74 reference statements)
4
54
0
Order By: Relevance
“…Given that the phosphorylation status of NMHC2A Tyr 158 regulates the dynamics of the actomyosin bundles, it is possible that the phosphorylation on Tyr 158 modulates the assembly and function of NM2 stacks, which are important for cytoskeleton remodeling and impact cell morphogenesis and migration [71]. The cellular mechanisms that drive morphogenesis depend on adhesion forces and on the activity of the actomyosin filaments [72], which are important in tissue wound healing and developmental closure events [73].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the phosphorylation status of NMHC2A Tyr 158 regulates the dynamics of the actomyosin bundles, it is possible that the phosphorylation on Tyr 158 modulates the assembly and function of NM2 stacks, which are important for cytoskeleton remodeling and impact cell morphogenesis and migration [71]. The cellular mechanisms that drive morphogenesis depend on adhesion forces and on the activity of the actomyosin filaments [72], which are important in tissue wound healing and developmental closure events [73].…”
Section: Discussionmentioning
confidence: 99%
“…Transverse arcs, on the other hand, are thin, contractile actomyosin bundles, arising through NMII-promoted condensing of the lamellipodial actin network at the cell edge (Burnette et al, 2011;Hotulainen and Lappalainen, 2006;Tojkander et al, 2011). Following their appearance, transverse arcs undergo retrograde flow towards the cell center, fuse with each other into thicker bundles, and become more contractile due to concatenation and persistent expansion of NMII filaments into stacks (Beach et al, 2017;Fenix et al, 2016;Hu et al, 2017;Jiu et al, 2019;Tojkander et al, 2015). Although transverse arcs are not directly linked to focal adhesions, they associate with focal adhesion -connected dorsal stress fibers (Burnette et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…the Rho-pathway, nonmuscle myosin II 7 (NM2) is assembled into minifilaments with approximately 30 single myosins [3,4], 8 forming a supra-molecular complex with a size around 300 nm that traditionally is 9 investigated with electron microscopy [5,6]. Only recently has live cell super-resolution 10 microscopy made it possible to image the dynamics of NM2-minifilaments in cells [7][8][9][10][11]. 11 This revealed many unexpected processes, including splitting, expansion, concatenation, 12 long-range attraction and stacking.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently has live cell super-resolution 10 microscopy made it possible to image the dynamics of NM2-minifilaments in cells [7][8][9][10][11]. 11 This revealed many unexpected processes, including splitting, expansion, concatenation, 12 long-range attraction and stacking. Moreover it was observed that single myosin 13 monomers have a relatively high exchange rate [10] and that the three human 14 NM2-isoforms A, B and C dynamically mix [12].…”
Section: Introductionmentioning
confidence: 99%